The Role of Rho GTPases in Toxicity of Clostridium difficile Toxins - Shuyi Chen; Chunli Sun; Haiying Wang; Jufang Wang (Toxins, 2015)
Clostridium difficile (C. difficile) is the main cause of antibiotic-associated diarrhea prevailing in hospital settings. In the past decade, the morbidity and mortality of C. difficile infection (CDI) has increased significantly due to the emergence of hypervirulent strains. Toxin A (TcdA) and toxin B (TcdB), the two exotoxins of C. difficile, are the major virulence factors of CDI. The common mode of action of TcdA and TcdB is elicited by specific glucosylation of Rho-GTPase proteins in the host cytosol using UDP-glucose as a co-substrate, resulting in the inactivation of Rho proteins. Rho proteins are the key members in many biological processes and signaling pathways, inactivation of which leads to cytopathic and cytotoxic effects and immune responses of the host cells. It is supposed that Rho GTPases play an important role in the toxicity of C. difficile toxins. This review focuses on recent progresses in the understanding of functional consequences of Rho GTPases glucosylation induced by C. difficile toxins and the role of Rho GTPases in the toxicity of TcdA and TcdB.